Distribution of Radiation Dosage to Organs at Risk (Oar) With Variations in Depth Brachytherapy Application in Cervical Cancer Patients (International Journal of Scientific Research in Science and Technology, 2024)
The accurate planning and selection of applicators are crucial in brachytherapy treatment to deliver radiation doses with high precision, ensuring maximum tumor targeting while minimizing doses to surrounding healthy organs. This study aims to evaluate the influence of changes in intrauterine applicator depth on the distribution of radiation doses in cervical cancer patients. Data were obtained from records of 30 patients undergoing brachytherapy treatment, comparing 10 patients with an initial applicator depth of 5 cm as a reference. The applicator depth was then adjusted to 4 cm and 6 cm through re-planning. Data analysis involved comparing average doses and calculating differences for each patient to determine the percentage change in applicator depth. Research findings indicate variations in radiation doses to organs at risk (OAR) concerning applicator depth. The highest average OAR doses occurred at a depth of 6 cm, while the lowest doses were at a depth of 4 cm. The difference in average doses at a 4 cm applicator depth was 2,49% for the bladder and 1,15% for the rectum. At a depth of 6 cm, the difference in average doses was 1,66% for the bladder and 1,72% for the rectum. The Wilcoxon signed-rank test (<0.05) revealed significant differences in doses between compared applicator depths.